Chromosome-Scale Assembly of the Dendrobium nobile Genome Provides Insights Into the Molecular Mechanism of the Biosynthesis of the Medicinal Active Ingredient of Dendrobium - Xu, Qing; Niu, Shan-Ce; Li, Kang-Li; Zheng, Pei-Ji; Zhang, Xiao-Jing; Jia, Yin; Liu, Yang; Niu, Yun-Xia; Yu, Li-Hong; Chen, Duan-Fen; Zhang, Guo-Qiang (Frontiers in Genetics, 2022)
Orchids constitute approximately 10% of flowering plant species. However, only about 10 orchid genomes have been published. Metabolites are the main way through which orchids respond to their environment. Dendrobium nobile, belonging to Dendrobium, the second largest genus in Orchidaceae, has high ornamental, medicinal, and ecological value. D. nobile is the source of many popular horticultural varieties. Among the Dendrobium species, D. nobile has the highest amount of dendrobine, which is regarded as one of the criteria for evaluating medicinal quality. Due to lack of data and analysis at the genomic level, the biosynthesis pathways of dendrobine and other related medicinal ingredients in D. nobile are unknown. In this paper, we report a chromosome-scale reference genome of D. nobile to facilitate the investigation of its genomic characteristics for comparison with other Dendrobium species. The assembled genome size of D. nobile was 1.19 Gb. Of the sequences, 99.45% were anchored to 19 chromosomes. Furthermore, we identified differences in gene number and gene expression patterns compared with two other Dendrobium species by integrating whole-genome sequencing and transcriptomic analysis (e.g., genes in the polysaccharide biosynthesis pathway and upstream of the alkaloid (dendrobine) biosynthesis pathway). Differences in the TPS and CYP450 gene families were also found among orchid species. All the above differences might contribute to the species-specific medicinal ingredient biosynthesis pathways. The metabolic pathway-related analysis will provide further insight into orchid responses to the environment. Additionally, the reference genome will provide important insights for further molecular elucidation of the medicinal active ingredients of Dendrobium and enhance the understanding of orchid evolution.